Effect on hypoglycemic activity and UPLC–MS/MS profiling of Rosa roxburghii fruit fermented with Chinese traditional distiller's yeast - YAN,Yanfang (2022)
Abstract To illuminate changes in the secondary metabolic spectrum and hypoglycemic activity between Rose roxburghii fruit fermented (RRFF) by Chinese traditional distiller’s yeast and R. roxburghii fruit (RRF) using UPLC–MS/MS and streptozotocin-induced diabetic mice. Secondary metabolomics in the RRFF apparently differs from those in RRF; 32 pentacyclic triterpenoids were identified first, and ursolic acid-substituted roxburix acids were found to be the marker compounds. Testing of HepG2 cells indicated that RRFF had good glucose consumption capacity. Additionally, fasting blood glucose levels, glucose tolerance tests, plasma insulin levels and insulin resistance in diabetic mice indicated that RRFF was better than RRF. More importantly, RRFF exhibited good structure in pancreatic tissue. These results indicate that the fermentation process is beneficial for increasing the content of triterpenoids and enhancing hypoglycemic activity. Traditional fermentation with Chinese traditional distiller’s yeast can provide a way to expand the application of nutritious fruits with short shelf life.